A new species of Ceradocus Costa, 1853 (Senticaudata: Maeridae) from Ceará State, Northeastern Brazil - Alves, Jessika; Johnsson, Rodrigo; Senna, André R. (Zootaxa, 2019)
A new species of the genus Ceradocus Costa, 1853 is described from Northeastern Brazil. This species is unique in having: (1) male gnathopod 2 propodus palm ornamented, palmar corner defined by a soft spine; (2) spines along the entire posterior margin of epimeral plate 3, (3) telson with very long apical setae. This new species is the second species of this genus in Brazil. An updated taxonomic key to the Ceradocus of the world is also provided.